Curvilinear effects of e-loyalty in China's online tourism industry. Issue 2 (5th June 2017) - Yang, Xueyan; Zhang, Xiaoni; Goh, Samuel; Anderson, Chad
Abstract : Purpose: The purpose of this paper is to understand e-loyalty in the travel industry. Specifically, this paper aims to examine the curvilinear relationship between predictors and e-loyalty. Design/methodology/approach: An empirical study was conducted using an online survey with one of the largest travel companies in China. Structural equation modeling was used to test the models, and pair-wise nested F-tests were used to compare the models. Findings: Results show that the curvilinear model has greater explanatory power of loyalty than traditional linear models. The results of pair-wise nested F-tests show that the loyalty model exhibits statistically significant R2 improvement compared to the linear model. However, the R2 improvement in the integrated model is not statistically different from that in the linear model. Confirmation and satisfaction are found to be salient factors influencing loyalty. Research limitations/implications: This study makes important contributions to the online community literature by understanding the drivers of loyalty in the travel industry. However, there are limitations. First, this study addressed member loyalty of an online travel community with data collected from one company. Thus, generalizability is limited. Online communities and firms may have different characteristics, resulting in different factors influencing consumer loyalty. The authors plan in the future to collect data from other online travel companies and examine their model with different samples so as to check the generalizability of the current findings. Second, the authors collected a snapshot view on loyalty. Both researchers and managers note that small changes in loyalty and retention can yield disproportionately large changes in profitability (Reichheld et al., 2000). Consumer loyalty may change over time, so to maintain and increase profits, it is important to monitor such change. In the future, the authors plan to conduct a longitudinal study of community members to evaluate their loyalty over time. Practical implications: As China seeks to gain additional market share in the global tourism market, travel companies should make use of websites as a marketing tool to attract and retain customers. These actions enable a travel company to enhance its competitiveness. More and more people use the internet for tour deals, bookings and finding tour-related information. Effective use of websites can affect the competitiveness of ecommerce companies. E-vendors could assess and adopt the dimensions recommended in this paper to help better understand areas for improvement. It is common today for consumers to buy travel products online instead of going through a travel agent. Considering the importance of reciprocity in formulating consumer satisfaction and loyalty in the virtual environment, companies should monitor reciprocal behavior on the virtual community. With advancement in technologies, consumer behaviors have changed and more consumers prefer social interactions in the virtual world. Companies can analyze posts in the virtual environment to assess reciprocity and may design a mechanism to foster reciprocal behaviors. By leveraging reciprocity, firms can better connect satisfaction with loyalty. More than 70 per cent of executives surveyed by McKinsey (2012) said that they regularly generate value through their Web communities. In addition, to pay attention to consumer to consumer reciprocity in the virtual world, companies should listen to what customers say in their online community, as this attention is an indication of reciprocity between consumers and companies. The ideas and opinions expressed in the online community tell the company customers' perception of the value of its products and customers' needs. Such attention to the voices in the online community will help companies to better tailor products/services to meet customers' needs. Furthermore, the voices expressed in the virtual community are also effective in developing and maintaining new internet marketing opportunities such as email marketing, giveaways, search engine optimization, pay per click and shopping comparison marketing. Companies interested in retaining and attracting customers should leverage their established virtual communities and pay close attention to online posts and evaluate members' satisfaction. Such effort will provide tangible benefits. As shown in Ye et al. 's study, traveler reviews produce a significant impact on online sales (Ye et al., 2011), with a 10 per cent increase in traveler review ratings, boosting online bookings by more than 5 per cent. This finding suggests that businesses should link online user-generated reviews to business performance in tourism. Finding incentives for users to share might be one way to improve interactivity and further create stickiness on the part of the website. Originality/value: This paper is one of the first studies to address the need to move beyond linear models of e-loyalty and to additionally examine potential curvilinear and interactive effects. This study also identifies key variables such as reciprocity and satisfaction as determinants of e-loyalty in the Chinese online travel and tourism industry.